Building Bridges: Toward Alternative Theory of Sustainable Supply Chain Management. Issue 1 (28th December 2015) - Matthews, Lee; Power, Damien; Touboulic, Anne; Marques, Leonardo
Abstract : We contend that the development of sustainable supply chain management (SSCM) theory has been impaired by a lack of paradigmatic diversity in the field. The contested nature of the concept of sustainability has been repressed in SSCM theory, which has led to SSCM cutting itself off from debates that could be the source of inspiration for the development of interesting theory. We adopt the problematization approach proposed by Alvesson and Sandberg (2011) in order to unveil some of SSCM's unquestioned assumptions, propose an alternative assumption ground, and in this way move toward stronger theory in SSCM. We use paradoxical framing to make sense of the inherent tensions between the different levels of sustainability and between the different types of theory being produced in response to the challenges of sustainability. We articulate a number of foundational assumptions for an alternative theory of SSCM that emerge from the various tensions identified between the different paradigms of sustainability. Finally, we identify a number of ideas for future research that would enable researchers to empirically explore the alternative assumptions.